Cadaveric Stem Cells: Their Research Potential and Limitations - Cieśla, Julia; Tomsia, Marcin (Frontiers in Genetics, 2021)
In the era of growing interest in stem cells, the availability of donors for transplantation has become a problem. The isolation of embryonic and fetal cells raises ethical controversies, and the number of adult donors is deficient. Stem cells isolated from deceased donors, known as cadaveric stem cells (CSCs), may alleviate this problem. So far, it was possible to isolate from deceased donors mesenchymal stem cells (MSCs), adipose delivered stem cells (ADSCs), neural stem cells (NSCs), retinal progenitor cells (RPCs), induced pluripotent stem cells (iPSCs), and hematopoietic stem cells (HSCs). Recent studies have shown that it is possible to collect and use CSCs from cadavers, even with an extended postmortem interval (PMI) provided proper storage conditions (like cadaver heparinization or liquid nitrogen storage) are maintained. The presented review summarizes the latest research on CSCs and their current therapeutic applications. It describes the developments in thanatotranscriptome and scaffolding for cadaver cells, summarizes their potential applications in regenerative medicine, and lists their limitations, such as donor’s unknown medical condition in criminal cases, limited differentiation potential, higher risk of carcinogenesis, or changing DNA quality. Finally, the review underlines the need to develop procedures determining the safe CSCs harvesting and use.